2019
DOI: 10.1016/j.molmet.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Insulin action in the brain regulates mitochondrial stress responses and reduces diet-induced weight gain

Abstract: Objective Insulin action in the brain controls metabolism and brain function, which is linked to proper mitochondrial function. Conversely, brain insulin resistance associates with mitochondrial stress and metabolic and neurodegenerative diseases. In the present study, we aimed to decipher the impact of hypothalamic insulin action on mitochondrial stress responses, function and metabolism. Methods To investigate the crosstalk of insulin action and mitochondrial stress r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 57 publications
0
52
0
Order By: Relevance
“…Furthermore, the use of antidiabetic drugs including metformin and GLP1 mimetics showed promising results in animal models of AD (Jha et al, 2017;Holscher, 2018). Moreover, considering that insulin signaling activation regulates mitochondrial functions (Butterfield et al, 2014a;Abad et al, 2019;Wardelmann et al, 2019) and that mitochondria are dysfunctional in DS (Mollo et al, 2020), it is conceivable to think rescuing insulin signaling activation in DS would be beneficial also with respect to mitochondrial performances. Metformin, a well-known drugs used to treat insulin resistance, was effective in recovering mitochondrial structure and functions in trisomic cells (Izzo et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the use of antidiabetic drugs including metformin and GLP1 mimetics showed promising results in animal models of AD (Jha et al, 2017;Holscher, 2018). Moreover, considering that insulin signaling activation regulates mitochondrial functions (Butterfield et al, 2014a;Abad et al, 2019;Wardelmann et al, 2019) and that mitochondria are dysfunctional in DS (Mollo et al, 2020), it is conceivable to think rescuing insulin signaling activation in DS would be beneficial also with respect to mitochondrial performances. Metformin, a well-known drugs used to treat insulin resistance, was effective in recovering mitochondrial structure and functions in trisomic cells (Izzo et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…We and others have demonstrated that IIS in adult female mosquitoes regulates egg production, longevity, defenses against infection, metabolism and the host stress response (Graf et al, 1997;Riehle and Brown, 1999;Riehle and Brown, 2002;Riehle and Brown, 2003;Lim et al, 2005;Kang et al, 2007;Roy et al, 2007;Brown et al, 2008;Sim and Denlinger, 2008;Arik et al, 2009;Corby-Harris et al, 2010;Horton et al, 2010;Gulia-Nuss et al, 2011;Marquez et al, 2011;Surachetpong et al, 2011;Pakpour et al, 2012;Hauck et al, 2013;Luckhart et al, 2013;Drexler et al, 2014;Arik et al, 2015;Pietri et al, 2016;Nuss and Brown, 2018). Further, substantial data indicate that IIS-dependent phenotypes are mediated through changes in mitochondrial function ( Figure 1) in model invertebrates, mosquitoes and in mammals (Toth et al, 2008;Cheng et al, 2010;Tiefenbock et al, 2010;Luckhart et al, 2013;Sadagurski and White, 2013;Drexler et al, 2014;Mukherjee et al, 2014;Pietri et al, 2016;Chaudhari and Kipreos, 2017;Ruegsegger et al, 2018;Wang et al, 2019;Wardelmann et al, 2019;Charmpilas and Tavernarakis, 2020;Sheard et al, 2020). Specifically, perturbations of both the IIS activator Akt and the inhibitor PTEN in the midgut of Anopheles...…”
Section: Insulin/insulin-like Growth Factor Signaling Controls Mitochmentioning
confidence: 93%
“…For instance, overexpression of insulin-like growth factors ( IGFs ) and receptors for insulin is associated with increased cell proliferation and risk of cancer [80]. Meanwhile, downregulation of insulin signaling contributes to proper mitochondrial function, suppression of inflammatory mediators, regulation of cellular metabolism, cellular resistance to stress, activation of DNA repair genes, and reduction of oxidative damage of macromolecules and cellular senescence, which all further enhance health and longevity, both in humans and other species [79,81,82]. In this respect, most anti-aging dietary interventions target growth-promoting pathways i.e., they function by downregulating IGF-1 and mTOR-S6K pathway and activating nutrient sensors ( MAPK and sirtuins), which signal nutrient scarcity and stimulate catabolism [83].…”
Section: Rj Might Enhance Longevity In Humans By Promoting Generalmentioning
confidence: 99%